SPATIAL DISTRIBUTION AND LOCATIONAL IMPLICATIONS OF PUBLIC CONVENIENCES IN KANO METROPOLIS - Ismail, Auwal Haruna; Abubakar, Ahmad Said; Bello, Nura Isyaku; Hussain, Ali (FUDMA JOURNAL OF SCIENCES, 2020)
This study is aimed at examining the spatial distribution and locational implications of public conveniences in Kano metropolis. This research utilized mixed methods; where both qualitative and quantitative methods were used. Both primary and secondary source of data were used in this study. The primary data were obtained from field measurementsile the secondary data were obtained from the Kano State Ministry of Environment, Kano State Urban Planning Development Authority (KNUPDA) as well as journals and previous theses. Materials used for this study include: Geo-positioning system (GPS) device (Garmin cx76 model) used for taking coordinates of the public conveniences (PCs). Computer software (Arc GIS 10.3) was also used in processing and analyzing of data generated from field. Availability sampling was used in administering questionnaires while purposive sampling was used for interview. The study find out that PCs are built rampantly without approval from appropriate government authoritymake them to build without complying with the standard rules and regulations. It is found that the distribution pattern of public PCs in Kano metropolis is mostly nucleated as they depend categorically on commercial activities as most of them are in motor parks or markets. This result also indicates that there is presence of air pollution and unsanitary condition due to poor drainage.
Keywords: Public Conveniences, spatial Distribution, Kano Metropolis